Cholecystoduodenal fistula without gallstones migration. Case report - Petracchi, Enrique; Canullan, Carlos; Posada, Héctor; Varela, José R (Cirugía del Uruguay, 2023)
Bouveret's syndrome is a rare cause of biliary ileus, with a high morbimortality. It is caused by the migration of a stone, usually large, into the gastrointestinal tract through a cholecystoduodenal fistula. The objective of this scientific letter is to present a patient with a previous stage of the disease where the fistula is constituted, but without migration of the calculus, so that the timely diagnosis would have a favorable impact on the treatment and prognosis because the obstructive intestinal condition is not established.